New insights into Chlamydia pathogenesis: Role of leukemia inhibitory factor - Wang, Jun; Wang, Katherine (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis (Ct) is the leading cause of bacterial sexually transmitted infections worldwide. Since the symptoms of Ct infection are often subtle or absent, most people are unaware of their infection until they are tested or develop severe complications such as infertility. It is believed that the primary culprit of Ct-associated tissue damage is unresolved chronic inflammation, resulting in aberrant production of cytokines, chemokines, and growth factors, as well as dysregulated tissue influx of innate and adaptive immune cells. A member of the IL-6 cytokine family, leukemia inhibitory factor (LIF), is one of the cytokines induced by Ct infection but its role in Ct pathogenesis is unclear. In this article, we review the biology of LIF and LIF receptor (LIFR)-mediated signaling pathways, summarize the physiological role of LIF in the reproductive system, and discuss the impact of LIF in chronic inflammatory conditions and its implication in Ct pathogenesis. Under normal circumstances, LIF is produced to maintain epithelial homeostasis and tissue repair, including the aftermath of Ct infection. However, LIF/LIFR-mediated signaling – particularly prolonged strong signaling – can gradually transform the microenvironment of the fallopian tube by altering the fate of epithelial cells and the cellular composition of epithelium. This harmful transformation of epithelium may be a key process that leads to an enhanced risk of infertility, ectopic pregnancy and cancer following Ct infection.